PENGARUH PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SEPATU OLAHRAGA MEREK SPECS DI KOTA BEKASI - Abdul Samad; Imam Wibowo (Jurnal Manajemen Bisnis Krisnadwipayana, 2016)
The research aimed to analyze effect of product and brand image on buying decision partially or simultanously. Research carried out for 3 months from January to March 2016. The questions are structured using Likert Scale with 80 respondents as sample.Based on regression analyze, it concluded that product positive and significant impact on buying decision. Brand image positive and significant impact on buying decision. Product and brand image simultaneously positive and significant on the buying decision.